Microcirculation - Piagnarelli, Michael (2012)
The microcirculation is the part of the circulation where oxygen, nutrients, hormones, and waste products are exchanged between circulating blood and parenchymal cells.The microcirculation includes not only all the vessels with a diameter <100 μm but also the interactions between blood components (circulating cells, coagulation factors), the vessels lined by the endothelium, and the glycocalyx.